Konsep dan Praktik Manajemen pada Masa Bani Umayyah - Padlianor; Muhammad Ibrahim Ash-Shiddieqy; Suraijiah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This research analyzes the concept and practice of management during the Umayyad Caliphate (661-750 AD), a crucial period in Islamic history. The dynasty established a vast empire from Spain to India, supported by an effective administrative and governmental management system. Muawiyah ibn Abi Sufyan, the first caliph, played a central role in developing an organized bureaucracy, military management, and an emphasis on justice and security. Yazid ibn Muawiyah’s reign continued efforts for political stability despite internal conflicts like the Karbala tragedy. Muawiyah ibn Yazid also contributed to socio-political stability and moderate state financial management. Umayyad government management advanced significantly by establishing various diwans (departments/offices) for military, finance, and postal affairs. The decentralization of power to governors reflected principles of division of labor and placing the right person in the right place. The legacy of Umayyad management, including structured administration and bureaucracy, remains relevant today in regional autonomy concepts and modern management principles